Synthesis, H- or J-type aggregations, electrochemistry and in situ spectroelectrochemistry of metal ion sensing lead(II) phthalocyanines - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
We report, in this study, peripherally 3- and 4-substituted functionalized ionophore ligands (1-3) and their alpha- and beta-tetra polyalcohol substituted lead(II) phthalocyanines M{Pc[S-CH(C3H7)(C2FH5OH)](4)} (7, 9 and 11) and M{Pc(S-C6H12(OH)](4)) (8. 10 and 12) which are a mixture of different isomers. The complexes have been fully characterized by elemental analysis, FT-IR, H-1 NMR, C-13 NMR, MS (MALDI-TOF) and UV-Vis spectral data. These complexes induced H-type (face-to-face fashion) on-aggregate (edgeto-edge) dimers when titrated with AgNO3 or Na2PdCl4 in a THF-MeOH solution. Cyclic and square wave voltammetry studies showed that the complexes gave three one-electron ligand-based reductions and two one-electron oxidation couples having diffusion controlled mass transfer character. Assignments of these redox couples were confirmed by spectroelectrochemical measurements. The observation of split Q bands, which are characteristic spectral behavior of metal-free phthalocyanines, indicates demetallization of the complexes during the spectroelectrochemical measurement under the applied potentials. The types of the substituents on the ring of the phthalocyanines affect the demetallization process of the complexes. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; Metal sensing; Lead; Aggregation; Cyclic voltammetry; Spectroelectrochemistry; Demetallization; RECEPTOR FUNCTIONAL PHTHALOCYANINES; PHOTOCHEMICAL PROPERTIES; PHOTOPHYSICAL PROPERTIES; COMPLEXES; SPECTROSCOPY; PORPHYRAZINES; DEMETALATION; SOLVENTS; BINDING